Co-infection with Mycobacterium bovis does not alter the response to bovine leukemia virus in BoLA DRB3*0902, genetically resistant cattle - Lützelschwab, Claudia María (2016)
High proviral load (HPL) profile in bovine leukemia virus infected animals poses increased risk of transmission, and development of HPL or low proviral load (LPL) profile may be attributed to host genetics. Genetic resistance and susceptibility has been mapped to the Major Histocompatibility Complex class II DRB3 gene (BoLA DRB3). The aim of this work was to determine the effect of Mycobacterium bovis infection on certain virological and host immunological parameters of BLV experimental infection. Twenty-six Argentinian Holstein calves carrying the resistance-associated marker allele BoLA DRB3*0902, susceptibility-associated marker allele BoLA DRB3*1501, or neutral BoLA DRB3 alleles, exposed to M. bovis were used. Twenty calves were inoculated with BLV, three were naturally infected and other three were BLV-negative. Seven from twenty six (27%) of the animals resulted positive to the PPD test. The proviral load, absolute leukocyte and lymphocyte counts, time to seroconversion, antibody titer against BLV, and viral antigen expression in vitro at various times post inoculation were determined and compared between PPD + and PPD − animals. From a total of 23 BLV positive animals (naturally and experimentally infected), 13 (56.5%) developed HPL, and 10 (43.5%) developed LPL. None of the investigated parameters were affected by infection with M. bovis. We concluded that the ability of cattle carrying resistance-associated marker to control BLV and to progress towards a LPL phenotype was not altered by M. bovis co-infection.